Higgs flavor violation as a signal to discriminate models - Lima, L. de [UNESP]; Machado, C. S. [UNESP]; Matheus, R. D. [UNESP]; Prado, L. A. F. do [UNESP] (Springer, 2015)
We consider the Higgs Lepton Flavor Violating process h -> tau mu, in which CMS found a 2.5 sigma excess of events, from a model independent perspective, and find that it is difficult to generate this operator without also obtaining a sizeable Wilson coefficient for the dipole operators responsible for tau radiative decay, constrained by BABAR to BR(tau -> mu gamma) < 4.4 x 10(-8). We then survey a set of representative models for new physics, to determine which ones are capable of evading this problem. We conclude that, should this measurement persist as a signal, type-III Two Higgs Doublet Models and Higgs portal-like models are favored, while SUSY and Composite Higgs models are unlikely to explain it.
Keywords: Higgs Physics; Rare Decays; Beyond Standard Model